The future of evaluation in society : a tribute to Michael Scriven - Donaldson, Stewart I.; Scriven, Michael (Evaluation in society, 2013)
The impetus for this volume lives in a rich and vibrant past. It is organized to honor one of the founders and most prolific contributors to the profession and transdiscipline of evaluation -- Professor Michael Scriven, and to illuminate the future of evaluation in society. Professor Scriven often shares stories of his meetings with Albert Einsten and the frame-breaking evaluation revolution he has led against the value free doctrine of the social sciences. Both his wide eyed graduate students and the more grizzled evaluation veterans in his professional development workshops quickly learn that Scriven is well traveled and has exchanged some of the boldest ideas and visions with the most brilliant thinkers of his time. Scriven insisted that the 2011 Stauffer Symposium and this volume be organized in that genre. He urged us to invite the most thoughtful and influential evaluation theorists and practitioners we could find to join him in a conversation about the future of evaluation in society.Scriven challenges us to examine the five great paradigm shifts that have revolutionized the foundations of evaluation, and that he believes will form the basis for a much brighter future for evaluation in society. Scriven's revolutionary ideas are followed and challenged by a group of thought leaders in evaluation who do not necessarily shared his views on evaluation, but who have earned his deepest respect and whose evaluation work he admires including Michael Quinn Patton, Ernest House, Daniel Stufflebeam, Robert Stake, Jennifer Greene, Karen Kirkhart, Melvin Mark, Rodney Hopson, and Christina Christie. However, despite his insistence that his colleagues stay focused on the future of evaluation, you will find that many have recounted their adventures, exchanges, and debates with him over the years, as well as pointed out the many contributions that he has made to the development of evaluation and to the improvement of society through his amazing portfolio of evaluation contributions.The Future of Evaluation in Society: A Tribute to Michael Scriven will be of great interest to evaluation scholars, practitioners, and students of evaluation. It will be appropriate for use in a wide range of evaluation courses including Introduction to Evaluation, Evaluation Theory, and Evaluation Practice courses.